The Correlation Between Students’ Remarkable Experiences and Their Ability in Recount Text Writing - Eka Rindi Astuti (Bandar Lampung University (UBL), 2014)
Junior high school students got many difficulties in recount text writing. They were difficult to tell past events or their experience in a good writing. Numbers of their experiences might support their recount-text writing. This research aimed to study if the numbers of the students’ experiences are correlated to their writing achievement. Because the term ‘experience’ has a very general concept, the writer limited it into remarkable experiences. An experience turns to be a remarkable one if it gets a significance of notice and attention from the sensor. This research was conducted to one group, which represented the grade-eight students of SMPN 20 Bandar Lampung. The group was selected with Cluster Sampling Technique. Data were collected with a questionnaire and writing test. Then, they were analyzed with r-Product Moment. Based on the computation, rxy: 0,618 was greater than the r-table in 1%: 0,449 and 5%: 0,349. Therefore, the alternative hypothesis (Ha) was accepted, while the null hypothesis (Ho) was rejected. The writer concluded that there was a correlation between students’ remarkable experience and their ability in writing recount text.